LES CLASSEMENT DES FAITS FOLKLORIQUES FRANÇAIS - Adizova , Obodon Istamovna (Innovative Development in Educational Activities, 2023)
The article describes the genre of folklore, its history and principles of development. It is based on the information about the origin, evolution, characteristics and structure of the folklore genre.